Zakat, Sustainability, and the SDGs: A Bibliometric Analysis and Systematic Mapping of Global Scholarship - Prasojoharto, Prayogo; Chariri, Anis; Purwanto, Agus (International Journal of Zakat, 2026)
PurposeThis study aimed to map and analyze the global scholarly landscape and thematic evolution within research integrating zakat with sustainability concepts and the Sustainable Development Goals (SDGs). Design/Methodology/Approach This research employed a bibliometric approach by analyzing 50 selected articles from the Scopus database spanning the period 2015-2025. Data were analyzed using VOSviewer software to perform co-authorship network mapping and keyword co-occurrence analysis. The PRISMA flow diagram was applied in the data selection process to ensure sample relevance and accuracy. FindingsThe results revealed a significant increase in publication volume since 2021, with contributions dominated by Malaysia and Indonesia. Thematic mapping identified three main clusters: (1) Islamic economics, zakat, and poverty; (2) the integration of zakat with SDGs and corporate sustainability; and (3) digitalization and the response to COVID-19. The study also identified limited international collaboration and a shift in research focus from conceptual approaches towards practical applications, particularly in digital accounting and corporate sustainability. Research limitations/implicationsThe primary limitation of this study lies in the use of the Scopus database as a single data source. Implications for future research include the need to expand data coverage to other databases, employ qualitative approaches to explore collaboration dynamics, and develop metrics to quantitatively measure the impact of zakat on SDG indicators. Practical implicationsThe findings recommend that zakat managers adopt digital technologies and strengthen governance to enhance program accountability and impact. For regulators, the results highlight the need for policy frameworks that support the integration of zakat into national development strategies and inter-institutional collaboration. Social implicationsThis study underscores the potential contribution of strategically managed zakat in supporting the achievement of the SDGs, particularly poverty alleviation and economic empowerment, which could ultimately enhance community welfare and social justice. Originality/valueTo the best of the authors' knowledge, this is the first bibliometric study to comprehensively map and analyze the evolution of the integration of zakat, sustainability, and the SDGs, thereby providing a foundational framework and a directed research agenda for the future development of this field.